Comparative Ability of Oropsylla montana and Xenopsylla cheopis Fleas to Transmit Yersinia pestis by Two Different Mechanisms. - B Joseph Hinnebusch; David M Bland; Christopher F Bosio; Clayton O Jarrett (Public Library of Science (PLoS), 2017)
BACKGROUND:Transmission of Yersinia pestis by flea bite can occur by two mechanisms. After taking a blood meal from a bacteremic mammal, fleas have the potential to transmit the very next time they feed. This early-phase transmission resembles mechanical transmission in some respects, but the mechanism is unknown. Thereafter, transmission occurs after Yersinia pestis forms a biofilm in the proventricular valve in the flea foregut. The biofilm can impede and sometimes completely block the ingestion of blood, resulting in regurgitative transmission of bacteria into the bite site. In this study, we compared the relative efficiency of the two modes of transmission for Xenopsylla cheopis, a flea known to become completely blocked at a high rate, and Oropsylla montana, a flea that has been considered to rarely develop proventricular blockage. METHODOLOGY/PRINCIPAL FINDINGS:Fleas that took an infectious blood meal containing Y. pestis were maintained and monitored for four weeks for infection and proventricular blockage. The number of Y. pestis transmitted by groups of fleas by the two modes of transmission was also determined. O. montana readily developed complete proventricular blockage, and large numbers of Y. pestis were transmitted by that mechanism both by it and by X. cheopis, a flea known to block at a high rate. In contrast, few bacteria were transmitted in the early phase by either species. CONCLUSIONS:A model system incorporating standardized experimental conditions and viability controls was developed to more reliably compare the infection, proventricular blockage and transmission dynamics of different flea vectors, and was used to resolve a long-standing uncertainty concerning the vector competence of O. montana. Both X. cheopis and O. montana are fully capable of transmitting Y. pestis by the proventricular biofilm-dependent mechanism.